Universalities in halo nuclei - Yamashita, Marcelo Takeshi [UNESP] (2010)
In this contribution I provide an overview of our group papers involving universalities in light exotic nuclei. It is also made a connection of these systems with some weakly bound ultracold molecules. © 2010 American Institute of Physics.